The Rights of Albanian Nationals under the Stabilization and Association Agreement between Albania and the European Communities - Gjevori, Anduena (Mediterranean Journal of Social Sciences, 2013)
This paper investigates the legal effects of the EU Association Agreements in the EU legal order and in the legal order ofAlbania with a special focus on the rights established for Albanian nationals by the Stabilization and Association Agreement(SAA). It first considers the legal effects of the EU Association Agreements in the EU legal order during the pre-accessionperiod. Such analysis shows that agreements between the Union and non-member states countries which follow the procedureprovided by Article 218 of the TFEU form part of the EU legal order. According to the ECJ, provisions of associationagreements can have direct effect provided that they contain a clear and precise obligation. Therefore, nationals of nonmemberstate countries party to an agreement with the EU can rely on the provisions of those agreements before the courts ofthe Member States. On the other hand, the legal effects of the SAA in the Albanian legal order during the pre-accession perioddepend on the interpretation of the Constitution from Constitutional Court especially of those provisions which concern therelationship of international law with national law and on the interpretation of the objectives of the SSA itself by national judges.Therefore, the second part of the paper will analyse the relationship of international and national law according to theconstitution and also the possibilities for supremacy and direct effect of the European law in the Albanian legal order. We willsupplement such analysis with recent Constitutional Court decisions, which address the problem of legal effects of EU law inthe Albanian legal order. The overall purpose of such analysis is to shed light on the citizen’s rights in regard to the so-calledpre-accession effect of EU law when the aspiring member state is on the way to full membership. This analytical perspective isimportant to both Albania and other South East European countries which are in the same legal position and are confusedabout the rights that their citizens gain from the SAA.